198 Effects of Corn Processing and Silage Inclusion Levels in Feedlot Diets on Steer Performance. (12th April 2022) - Meier, Nolan R; Wilke, Karla; Erickson, Galen E; Loza, Pablo
Abstract: Feedlot steers (n = 480, initial BW = 389 kg ± 17 kg) were used to test the interaction between corn processing and silage inclusion on the performance and carcass characteristics. Treatments were designed as a 2 × 4 factorial design experiment with factors as 2 corn processing methods (dry-rolled corn, DRC, and steam-flaked corn, SFC) and 4 inclusions of silage (0, 15, 30, 45% of diet DM). Diets also contained 10% MDGS and 5% supplement. Steers were blocked by BW, assigned randomly to pens, and data analyzed using MIXED procedure of SAS with block fixed and pen (n = 48) as the experimental unit. Steers were fed the same days for all treatments (125 d). No significant interactions were observed between corn processing and silage inclusion for performance or carcass characteristics ( P > 0.12), therefore, main effects will be presented. As silage inclusion increased, intake (DMI), gain (ADG), and feed efficiency (G:F) changed quadratically ( P < 0.03). Gains were greater for cattle fed 15 or 30% silage and lower diets with 0 or 45% silage. Feed efficiency was greatest for steers fed 0% silage (0.168) and decreased to 0.161 and 0.152 as silage inclusion increased to 15 and 30% inclusion. The quadratic response is due to decreased G:F for steers fed 45% silage (0.139). Carcass characteristics responded similar to ADG quadratic ( P < 0.01) impacts on fat depth and marbling. Feeding SFC in comparison to DRC led to increased DMI, ADG, G:F, and fat depth ( P < 0.04). Gains were greater for cattle fed SFC than cattle fed DRC, which led to increased G:F (SFC = 0.160, DRC = 0.151) across all silage inclusions. Increasing silage inclusion resulted in greater ADG, marbling, and fat depth with 15 and 30% compared with 0 and 45%. Feeding SFC improved performance compared with DRC.